Pemanfaatan ampas limbah industri agar-agar (Gracilaria sp.) pada pembuatan kertas map eceng gondok (Eichhornia crassipes): Utilization of agar-agar industry waste (Gracilaria sp.) in the production of map paper from water hyacinth (Eichhornia crassipes) - Patricia, Angelina Sherly Nur; Dewi, Eko Nurcahya; Susanto, Eko; Purnamayati, Lukita (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Annually, the agar processing industry (Gracilaria sp.) continues to increase the amount of waste pulp it produces. Cellulose, present in agar pulp, serves as a raw material for the production of folder paper. The purpose of this study was to determine the best concentration of industrial waste pulp based on the characteristics of water hyacinth folder paper. The study used an experimental lab with a complete randomized design (CRD) to test how different concentrations of agar pulp affect the process of making folder paper. These concentrations were 0, 10, 15, and 20%. The test parameters of the folder paper are grammage, tear resistance, water absorption, stiffness, hedonic, and SEM. Adding more agar pulp to the folder paper made it more resistant to tears and better at absorbing water, but it made it less dense, stiff, and enjoyable to use. The optimal outcome was achieved with the addition of 20% agar processing pulp. It had a weight of 318.67 g/m2, a tear resistance of 1573.3 mN, a water absorption of 926.3 g/m2, a stiffness of 45 g/m3, and a hedonics value of 6.82±< 6.83. The absorption in the 928–933 cm⁻³ band shows that the 3,6-anhydrogalactose group of agar-agar constituent compounds is present.